B cells help alloreactive T cells differentiate into memory T cells - Ng, Yue-Harn (2010)
B cells are recognized as effector cells in allograft rejection that are dependent upon T cell help to produce alloantibodies causing graft injury. It is not known if B cells can also help T cells differentiate into memory cells in the alloimmune response. We found that in B cell-deficient hosts, differentiation of alloreactive T cells into effectors was intact whereas their development into memory T cells was impaired. To test if B cell help for T cells was required for their continued differentiation into memory T cells, activated T cells were sorted from alloimmunized mice and transferred either with or without B cells into naïve adoptive hosts. Activated T cells co-transferred with B cells gave rise to more memory T cells than those transferred without B cells and upon recall, mediated accelerated rejection of skin allografts. Co-transfer of B cells led to increased memory T cells by enhancing activated CD4 T cell proliferation and activated CD8 T cell survival. These results indicate that B cells help alloreactive T cell differentiation, proliferation and survival to generate optimal numbers of functional memory T cells.